Beautiful past awaits us: Time and individual memory in contemporary art (Papers in Arts and Humanities, 2022)
Grasping the concept of transience or time has been a basic theme in art; hence it is no surprise that Proust also tried to search for the lost time. However, many people try the impossible: to capture the ephemeral. In any case, transience is a fundamental theme of art, although its representability is always questionable. As Jauss (1952/1996) writes, “time has a special relationship with narrative art” (p. 5). However, the notion of time is inherently difficult to define. As St. Augustine’s saying goes—which now has become a catchphrase—“What then is time? If no one asks me, I know; if I want to explain it to a questioner, I do not know” (Augustine, 2006, p. 242). According to Henri Bergson (1889) time is the central question of metaphysics. If this puzzle were solved, everything would be solved. Time is perceived only in its transience. Borges wrote “time is the substance I am made of” (1956–1960/1964, p. 234). The static nature of visual art—prevalent until videos and video installations emerged—makes it particularly problematic to show a phenomenon that can only be perceived in its transience. The great challenge for art is how to depict this elusiveness. The eternal question is how we can be the same and yet different. What remains is memory. Memories are partly individual, and it is largely memories that constitute us. Thus, the topic of my paper is the representation of time, more precisely that of the passing of time, and of memories in contemporary art and the possible attitudes of the artists to stop the past, since remembering is also a rewriting and reinterpretation of the past.
Keywords: time; transience; memory; rewriting; contemporary art